Temporal and spatial analysis of event-related potentials in response to color saliency differences among various color vision types - Takahashi, Naoko; Sawayama, Masataka; Chen, Xu; Motomura, Yuki; Takeichi, Hiroshige; Miyauchi, Satoru; Hiramatsu, Chihiro (Frontiers in Human Neuroscience, 2024)
Human color vision exhibits significant diversity that cannot be fully explained by categorical classifications. Understanding how individuals with different color vision phenotypes perceive, recognize, and react to the same physical stimuli provides valuable insights into sensory characteristics and promotes mutual understanding. This study aimed to identify behavioral and neural differences between different color visions, primarily classified as typical trichromats and anomalous trichromats, in response to two chromatic stimuli, blue-green and red, during an attention-demanding oddball task. We analyzed the P3 component of event-related potentials (ERPs), associated with attention, and conducted a broad spatiotemporal exploration of neural difference. In typical trichromats, more rapid potentiation from the occipital to parietal regions was observed in response to the more salient red stimulus, particularly in the area overlapping with the P3 component. In anomalous trichromats, exploratory analysis revealed faster potentiation in response to the expected more salient blue-green stimulus in the occipital to parietal regions, with no other significant neural differences between stimuli. Comparisons between color vision types showed no significant differences in overall neural responses. The large variability in red-green sensitivity among anomalous trichromats, along with neural variability not fully explained by red-green sensitivity, likely contributed to the absence of clear neural distinctions based on color saliency. While reaction times were influenced by red-green sensitivity, neural signals showed ambiguity regarding saliency differences. These findings suggest that factors beyond red-green sensitivity influence neural activity related to color perception and cognition in minority color vision phenotypes. Further research with a larger sample size is needed to explore these neural dynamics comprehensively.